Analysis of Serum Uric Acid Level in Patients with and without Diabetic Nephropathy - Erika Rosaria Simbolon; Suci Aprianti; Nurahmi Nurahmi; Liong Boy Kuniawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Diabetic nephropathy is one of the microvascular complications in type 2 Diabetes Mellitus (DM). Diagnosis of diabetic nephropathy is based on any history of DM, a decrease in Glomerular Estimation Filtrate Rate (eGFR) using the CKD-Epi formula, and albuminuria. The role of serum uric acid level in diabetic nephropathy remains an ongoing debate. Serum uric acid levels may be the cause or the result of diabetic nephropathy. This study aimed to analyze serum uric acid levels in patients with and without diabetic nephropathy and determine its correlation with diabetic nephropathy. This study was performed at Dr. Wahidin Sudirohusodo Hospital, Makassar, by taking the data from the medical record of type 2 DM patients from January to April 2018. Fifty-nine patients with diabetic nephropathy and 150 patients without diabetic nephropathy participated in this study. An independent T-test and Pearson's correlation test were used for statistical analysis. There was a significant difference in uric acid level between patients with and without diabetic nephropathy (9.57±3.42 mg/dL vs. 6.41±2.86 mg/dL, p < 0.001). There was significant correlation between uric acid serum levels with urea (p < 0.001, r=0.585), creatinine (p<0.001, r=0.413) and eGFR (p < 0.001, r=-0.525) in patients with diabetic nephropathy. Uric acid levels in patients with diabetic nephropathy were higher than patients without diabetic nephropathy. Higher levels of urea and the serum creatinine led to higher levels of serum uric acid. Contrastingly, a lower eGFR rate led to higher levels of uric acid.